The Global Status of Physical Activity in the Prevention of Childhood Obesity - Abigail Duffine Gilman; Stella Lucia Volpe (Pensar en Movimiento)
Childhood obesity is a public health concern that threatens the health and well-being of children worldwide and is associated with several of their chronic health conditions. Although a positive energy balance leads to excess body weight in children, there are several factors that influence their weight status. Dietary intake and physical activity greatly contribute to the energy balance in children. Mental health is also associated with their weight status and physical activity. Further, race and ethnicity, family structure, and the built environment contribute to the amount of physical activity achieved by children. One purpose of the current review is to summarize the connection between physical activity and weight status in children, and highlight key factors influencing this relationship, such as mental health and race, ethnicity, family structure and the built environment. Another purpose of this review is to highlight interventions and policies that may influence the relationship between physical activity and weight status in children. Policies that influence the surrounding environment may enhance children’s accessibility for physical activity and affect neighborhood safety, the density of supermarkets and commercial physical activity facilities available, as well as the provision of structured physical activity opportunities for children. Policies that influence the school environment also provide the opportunity to facilitate additional physical activity for students. Therefore, the overall purpose of this review is to discuss the many factors that influence weight status in children and provide ideas for future research.